Love as a criterion for valuating experiences of Montessori class graduates - Beata Bednarczuk (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Montessori claimed that love is a key concept that cannot be defined, but nevertheless treated it as central to life and education and therefore wrote a lot about its nature. Studies conducted by the Italian researcher facilitated finding the source of love, which is the child Consequently, the didactic system she developed is focused on the child Feelings and emotions are a kind of ability to reflect, an element of a wider system of information processing. Attributing emotional value to specific events is a specific process of creating meanings For research purposes, the knowledge was obtained that allowed to determine a profile of 24 feelings for school experiences as well as general and ideal feelings of Montessori class graduates, expressed as valuations. It was established whether the school as well as general and ideal experiences have a positive, negative or ambivalent value for the respondents.